Down's syndrome patient with multiple sialoliths in Stenson's duct - Jayant Palaskar; Sangeeta Palaskar; Nikhil Joshi (Wolters Kluwer Medknow Publications, 2012)
The presence of multiple sialoliths (calculi) in parotid duct is considered extremely rare. Parotid duct sialoliths are usually small and single. Multiple calculi formation, in any case, is an uncommon finding in the salivary glands. Salivary lithiasis is comparatively common in the Wharton's duct due to its tortuous ascending course and chemical composition of saliva of submandibular gland. The mechanism of sialolith formation in Down's syndrome patients is not completely known, and there are seldom cases reported in the literature available. The present case report is a very rare combination of a Down's syndrome with multiple sialoliths in Stenson's duct of left parotid gland in a 21year old male patient.